2019
DOI: 10.1007/s13311-019-00733-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Imaging of Lipid-Shelled Microbubbles for Ultrasound-Triggered Release of Xenon

Abstract: Xenon (Xe) is a bioactive gas capable of reducing and stabilizing neurologic injury in stroke. The goal of this work was to develop lipid-shelled microbubbles for xenon loading and ultrasound-triggered release. Microbubbles loaded with either xenon (Xe-MB) or xenon and octafluoropropane (Xe-OFP-MB) (9:1 v/v) were synthesized by high-shear mixing. The size distribution and the frequency-dependent attenuation coefficient of Xe-MB and Xe-OFP-MB were measured using a Coulter counter and a broadband acoustic attenu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 65 publications
0
14
0
Order By: Relevance
“…An ultrasound microbubble contrast agent is a liquid solution containing bubbles with a diameter between 1 and 8 μ m, which are injected into human blood vessels to enhance the ultrasound signal of blood flow, thereby improving the clarity and resolution of resulting ultrasound images [ 9 , 10 ]. Due to the limited flexibility of human blood cells and the ability of microbubbles to increase the spacing between human tissues, the microbubbles can enhance ultrasound signals.…”
Section: Introductionmentioning
confidence: 99%
“…An ultrasound microbubble contrast agent is a liquid solution containing bubbles with a diameter between 1 and 8 μ m, which are injected into human blood vessels to enhance the ultrasound signal of blood flow, thereby improving the clarity and resolution of resulting ultrasound images [ 9 , 10 ]. Due to the limited flexibility of human blood cells and the ability of microbubbles to increase the spacing between human tissues, the microbubbles can enhance ultrasound signals.…”
Section: Introductionmentioning
confidence: 99%
“…112 Interestingly, Shekhar et al demonstrated effective encapsulation and ultrasound-triggered (6 MHz Doppler, MI 0.8 and 220 kHz pulsed, MI 0.47, 10 seconds) delivery of xenon to the brain in a mouse model using a DSPC/DSPE-PEG2000 (9 : 1 ratio) lipid-shelled microbubble loaded with xenon and octafluoropropane, to help reduce and stabilize neurologic injury in stroke. 113 Most excitingly, since 2018, several small (4-5 patients per study) phase I safety and feasibility studies on permeabilizing the BBB in humans using focused ultrasound techniques have been reported with no serious clinical or radiological side effects. [114][115][116] A representative image from one of these studies, demonstrating visible BBB opening, is shown in Fig.…”
Section: Reviewmentioning
confidence: 99%
“…To prepare NO-loaded MB, 1,2distearoyl-sn-glycero-3-phosphocholine (DSPC), and 1,2distearoyl-sn-glycero-3-phosphoethanolamine-N-[methoxy (polyethylene glycol)-2000] (18:0 PEG2000 PE) were combined in a molar ratio of 9:1. The procedure for preparing these lipidshelled MB has been reported in detail previously (Shekhar et al, 2019b). Briefly, a thin lipid film was formed in a round bottom flask using a rotary evaporator (N-1001, Eyela, Bohemia, NY).…”
Section: Preparation Of Lipid-shelled Mbmentioning
confidence: 99%
“…Recent studies on bioactive gas delivery suggest that the bioactive gas payload can be stabilized by the co-encapsulation of perfluorocarbon gases (Kwan et al, 2012;Yang et al, 2018;Shekhar et al, 2019b). Whether co-encapsulation of a perfluorocarbon gas can stabilize NO payload within MB has not been determined previously.…”
Section: Introductionmentioning
confidence: 99%